1980
DOI: 10.1159/000181949
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal Blood Flow Distribution in the Genetically Hypertensive Rat

Abstract: Distribution of intrarenal blood flow has been measured in genetically hypertensive (GH) and normotensive (N) rats (aged 17–23 weeks) by a 133Xe washout technique without opening the abdominal cavity. Three different specific flow compartments were found in the rats. The distribution of the intrarenal blood flow to the fast compartment was reduced in the GH rats when compared with the N rats and the rate of flow in it was also reduced. The flow rate in the second compartment was the same in the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(21 reference statements)
1
1
0
Order By: Relevance
“…Renal blood flow was 30% lower in both young and adult GH rats compared with N rats. This confirms previous observations in adult GH rats 34 and supports the trend reported by Baer et al 35 . in 4‐week‐old GH rats.…”
Section: Discussionsupporting
confidence: 93%
“…Renal blood flow was 30% lower in both young and adult GH rats compared with N rats. This confirms previous observations in adult GH rats 34 and supports the trend reported by Baer et al 35 . in 4‐week‐old GH rats.…”
Section: Discussionsupporting
confidence: 93%
“…21 In addition, a recent study showed reduced renal blood flow per unit mass of kidney tissue in the New Zealand SHR and a reduced distribution and flow to the outer cortical compartment. 29 The 6-week-old SHR has a lower renal blood flow and greater preglomerular pressure drop. 30 -3I These findings suggest a preglomerular vascular origin, which emphasize the possible role of the kidney in the pathogenesis of hypertension in the SHR.…”
Section: Afferent Arteriolar Findingsmentioning
confidence: 99%